MADREBOT: A VIRTUAL LEARNING ENVIRONMENT SUPPORTED BY NEW TECHNOLOGIES - Freitas Barroso, Ari (Revista Gênero e Interdisciplinaridade, 2023)
In this work, the theoretical basis that underpins the research is discussed, in which Vygotsky’s work is emphasized. Thus, a Virtual Learning Environment (VLE) was developed that provides an Educational Chatterbot. Chatterbots are programmed robots that simulate a conversation. This technological tool presents the new school and focuses on Concepts about Ecology